Development, validation, and application of a novel tool to measure disease-related knowledge in patients with inflammatory bowel disease - Yoon, Hyuk (Korean J Intern Med, 2019)
BACKGROUND/AIMS: The Crohn’s and Colitis Knowledge (CCKNOW) score does not reflect updated knowledge relating to inflammatory bowel disease (IBD). The aim of this study was to develop, validate, and apply a novel tool to measure disease-related knowledge in IBD patients. METHODS: A questionnaire composed of 24 items regarding knowledge of IBD was developed: Inflammatory Bowel Disease Knowledge (IBD-KNOW). Discriminate ability of IBD-KNOW was validated in three occupational groups (14 doctors, 20 nurses, and 19 clerks). The CCKNOW and IBD-KNOW were administered to IBD patients. Factors affecting the level of IBD-related knowledge were analyzed. RESULTS: The median Inflammatory Bowel Disease Knowledge (IBD-KNOW) score was significantly different among the three groups for validation (22 doctors, 20 nurses, and five clerks; p < 0.001). The IBD-KNOW showed excellent internal consistency (Cronbach α = 0.952) and high correlation with CCKNOW (Spearman ρ = 0.827, p = 0.01). A total of 200 IBD patients (120 Crohn’s disease, 80 ulcerative colitis) completed questionnaires. Multivariate analysis showed that a higher IBD-KNOW score than the median was associated with hospitalization history (odds ratio [OR], 2.625; p = 0.003), high education level (OR, 2.498; p = 0.012), and information acquired from patient organization (OR, 3.305, p = 0.035). CONCLUSIONS: The IBD-KNOW demonstrated excellent test characteristics. Hospitalization history, education level, and information acquired from patient organization play an important role in correct IBD-related knowledge.